A reference constructicon as a database - Patel, Malin; Garibyan, Armine; Winckel, Elodie; Evert, Stephanie (Yearbook of the German Cognitive Linguistics Association, 2023)
This article explores the importance of database architecture in building a reference constructicon. Several reference constructicons have been implemented for various languages (FrameNet Constructicon, English Constructicon, Japanese FrameNet Constructicon, German Constructicon, Swedish Constructicon, FrameNet Brasil Constructicon, Russian Constructicon). However, most constructicon projects do not provide explicit information about their implementation or the underlying data model. A recent reference constructicon project dealing mainly with the English language is CASA (Construction Grammar Approach to Syntactic Analysis). In this paper, we present the data model underlying CASA in detail and its current implementation as a relational database and web interface. Relational databases are widely used for many different applications and allow large amounts of data to be stored and managed in a structured and efficient way.<br
Keywords: constructicon; database; Construction Grammar; constructicography; implementation

Discourse-based constraints on long-distance dependencies generalize across constructions in English and French - Winckel, Elodie; Abeillé, Anne; Hemforth, Barbara; Gibson, Edward (Cognition, 2025)
The article presents four acceptability judgment experiments that evaluate novel predictions of the Focus-Background Conflict constraint (Abeillé et al. 2020, Cognition) with respect to the acceptability of long distance dependencies for so-called “subject islands” in English and French. In contrast with syntactic accounts, the Focus-Background Conflict constraint predicts differential behavior across different constructions. The current paper tests a novel prediction of this theory, in a construction that has not yet been tested experimentally: it-clefts. Experiment 1 shows that elements in clefted clauses are not uniformly backgrounded, contrary to a standard assumption in the syntax / discourse literature. Experiments 2–4 tested long-distance dependency relations in relative clauses and clefts. In both languages, there is strong evidence of a cross-construction difference when comparing the two constructions with each other: extraction of the subject complement out of a subject NP was super-additively difficult in clefts, but not in relative clauses, as predicted by the Focus-Background Conflict constraint.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Clefts; English; Filler-gap constructions; French; Information structure; Subject islands

French subject islands. Empirical and formal approaches - Winckel, Elodie (Language Science Press, 2024)
This book examines extractions out of the subject, which is traditionally considered to be an island for extraction. There is a debate among linguists regarding whether the “subject island constraint” is a syntactic phenomenon or an illusion caused by cognitive or pragmatic factors. The book focusses on French, that provides an interesting case study because it allows certain extractions out of the subject despite not being a typical null-subject language. The book takes a discourse-based approach and introduces the “Focus-Background Conflict” constraint, which posits that a focused element cannot be part of a backgrounded constituent due to a pragmatic contradiction. The major novelty of this proposal is that it predicts a distinction between extractions out of the subject in focalizing and non-focalizing constructions. The central contribution of this book is to offer the detailed results of a series of empirical studies (corpus studies and experiments) on extractions out of the subject is French. These studies offer evidence for the possibility of extraction out of the subject in French. But they also reveal a clear distinction between constructions. While extractions out of the subject are common and highly acceptable in relative clauses, this is not the case for interrogatives and clefts. Finally, the book proposes a Head-Driven Phrase Structure Grammar (HPSG) analysis of subject islands. It demonstrates the interaction between information structure and syntax using a representation of information structure based on Minimal Recursion Semantics (MRS).

Language Analytic Ability, Print Exposure, Memory and Comprehension of Complex Syntax by Adult Native Speakers - Winckel, Elodie; Dabrowska, Ewa (Journal of Cognition, 2024)
Nativist theories of language development assume that all native speakers of a particular language ultimately converge on (more or less) the same grammar, and argue that this is only possible because they are born with a genetic blueprint for language. However, a number of recent studies have found that there are, in fact, considerable individual differences in adult native speakers’ grammatical attainment. In this study, we examine some possible reasons for these differences. We examine both learner internal cognitive factors (implicit and explicit memory for sequences, non-verbal working memory, and language analytic ability) as well as an experiential factor (print exposure). In contrast to many earlier studies which focused on the temporal aspects of language processing, we are interested in the extent to which individuals are able to use grammatical cues to extract meaning from complex sentences. To minimize the effect of performance factors, sentences remained on screen while participants responded to comprehension questions (thus easing working memory load) and participants were given as much time as they needed to respond. Our findings revealed large effects of language analytic ability and print exposure, and a much smaller effect of implicit learning. While the effect of implicit learning fits in well with current theories of language acquisition and processing, the first two findings do not. The strong relationship between print exposure and comprehension suggests that the ability to process complex syntax may depend on a particular type of language experience which is not available to all speakers. Finally, the effect of language analytic ability challenges the wide-held conviction that the ability to identify and explicitly reason about linguistic patterns is only relevant in adult second language learnin
Keywords: individual differences; grammar; comprehension; language aptitude; language analytic ability; memory

Structural, Functional, and Processing Perspectives on Linguistic Island Effects - Liu, Yingtong; Winckel, Elodie; Abeillé, Anne; Hemforth, Barbara; Gibson, Edward (Annual Review of Linguistics, 2022)
Ross (1967) observed that “island” structures like “Who do you think [NP the gift from__] prompted the rumor?” or “Who did you hear [NP the statement [S that the CEO promoted__]]?” are not acceptable, despite having what seem to be plausible meanings in some contexts. Ross (1967) and Chomsky (1973) hypothesized that the source of the unacceptability is in the syntax. Here, we summarize how theories of discourse, frequency, and memory from the literature might account for such effects. We suggest that there is only one island structure—a class of coordination islands—that is best explained by a syntactic/semantic constraint. We speculate that all other island structures are likely to be explained in terms of discourse, frequency, and memory.
Keywords: syntactic islands; long-distance dependencies; filler-gap dependencies; discourse constraints; usage-based grammar; syntactic constructions; Focus–Background Conflict; linguistic interference; linguistic encoding

The acquisition of constructions: Does modality matter? - Wright, Richenda; Geertsema, Salomé; le Roux, Mia; Winckel, Elodie; Dabrowska, Ewa (Reading & Writing, 2024)
Background: Language analytic ability is well researched in the context of foreign language acquisition but its role in the acquisition of grammar in the native language is under investigation. Objectives: Our study explored the influence of language analytic ability and print exposure on receptive grammar and reading comprehension in childhood. Additionally, we investigated whether exposure to specific constructions through the written modality held an advantage over exposure in the audio modality. Method: We assessed the language analytic ability, reading comprehension, reading fluency, print exposure, and receptive grammar of 12-year-olds. Subsequently, we exposed them to written or spoken target constructions, followed by an assessment of receptive grammar. Linear regression models were used to analyse the contributions of reading fluency, print exposure, and language analytic ability to reading comprehension and receptive grammar. We also examined the influence of the intervention on receptive grammar. Results: Language analytic ability and print exposure significantly predicted receptive grammar. Print exposure significantly predicted reading comprehension and improvement in receptive grammar. Conclusion: Language analytic ability is important for grammar and reading comprehension development. Print exposure enhances reading comprehension by supporting vocabulary development and providing exposure to intricate structures. Both language analytic ability and experience are key factors in construction acquisition. Contribution: This study adds to the growing body of evidence emphasising the role of language analytic skills in native language grammar acquisition and advocates for explicit grammar teaching. Furthermore, it underscores the importance of adequate print exposure in grammar acquisition and the development of reading comprehension skills.<br
Keywords: literacy; print exposure; language aptitude; grammar; language analytic ability